2018
DOI: 10.1177/1550147718805689
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and adaptive multi-path routing algorithm based on software-defined network

Abstract: Recently, there has been a surge of the video services over the Internet. However, service providers still have difficulties in providing high-quality video streaming due to the problem of scheduling efficiency and the wide fluctuations of end-toend delays in the existing multi-path algorithms. To solve these two problems affecting video transmission quality, networks are expected to have the capability of dynamically managing the network nodes for satisfying quality-of-service requirements, which is a challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…They only incorporate the latency of the paths while making their routing decisions. In [14], the authors propose a multipath routing algorithm that finds a path of least cost that satisfies the delay and bandwidth constraint. However, these approaches have high route computation time and a large number of forwarding entries because of generating routes for every source-destination pair and QoS policy.…”
Section: Other Approaches For Routing In Software-defined Overlay mentioning
confidence: 99%
See 1 more Smart Citation
“…They only incorporate the latency of the paths while making their routing decisions. In [14], the authors propose a multipath routing algorithm that finds a path of least cost that satisfies the delay and bandwidth constraint. However, these approaches have high route computation time and a large number of forwarding entries because of generating routes for every source-destination pair and QoS policy.…”
Section: Other Approaches For Routing In Software-defined Overlay mentioning
confidence: 99%
“…One of the main challenges in software-defined overlay networks is the fast-changing overlay link QoS characteristics because of various reasons like the change in the corresponding path in the physical network or the change in non-overlay back-ground Internet traffic [14]. However, the existing routing algorithms for satisfying multiple QoS constraints in software-defined overlay networks involve high route computation time and thus these routing algorithms cannot adapt to the fast-changing overlay link QoS characteristics [8]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…Jiawei et al 45 have presented adaptive communication architecture for WSNs which resolves the problem of communication in heterogeneous networks. The architecture adapts a wide range of communication mechanisms from the transport layer to the MAC layer without changing the protocols or applications.…”
Section: Layered Architecturementioning
confidence: 99%
“…Thus, in [12], conventional routing protocols such as RIP, OSPF, EIGRP, and BGP, are compared with SDN with respect to convergence times after link failures, showing that SDN routing is better than conventional IP networks. Considerable work has also shown that SDN can select routing paths based on criteria such as quality of service (QoS) [13][14][15][16], while energy-aware SDN routing has also been discussed in several papers [17][18][19].…”
Section: Introductionmentioning
confidence: 99%